Morphometric and hydrological characteristics of Abo-Habil Basin, western Sudan - Ahmed, Ummhani Idris (Journal of natural sciences, life and applied sciences, 2024)
Examining morphometric parameter is essential for understanding hydrological processes and watershed management, with the goal of utilizing water for various purposes. The primary objective of this research is to identify the morphometric characteristics of the Abo-Habil Basin in western Sudan, analyze the hydrological network of the basin and its significance, and focus on how natural elements have shaped the basin and their impact on flood-prone areas, which can lead to loss of life and property. Additionally, this study employs Geographic Information Systems (GIS) technology for data collection and analysis to establish a database of morphometric characteristics and their hydrological parameters in this region. The analytical descriptive method is utilized to describe the physical characteristics of the basin, including climatology and geology, while a quantitative approach is employed to develop a morphometric database. This includes quantitative analyses of the basin's characteristics, such as aerial, topographic, and drainage network data, using Digital Elevation Models (DEM) and Landsat 8 imagery to derive hydrological parameters. Findings indicate that the valley is situated in a desert climate zone, both arid and semi-arid. The morphometric analysis reveals that the valley trends toward a central location or an endpoint of the watershed, potentially leading to a primary river or drainage region. Additionally, the analysis shows the morphology and arial characteristics of the basin, , presented in Table( 10) including an area of approximately (30211.8) km², a perimeter of (1356.4) km, a length of (374) km, width basin ( 233), an elongation ratio of (0.5), a circularity ratio of (0.2) and a form factor of (0.2). The drainage network analysis of the Abo-Habil basin, presented in Table( 12), reveals five orders, ranging from 1st order (the smallest tributaries) to 5th order (the largest one), with a dendritic drainage pattern.The total Stream length of drainage network is (7271) km, with average bifurcation ratio of ( 5.13) and a hypsometric integral of (19.6%).Relief basin characteristics presented in Table (11). The Abo-Haibl basin has a total relief of (1082) m, a relief ratio of  (2.9 )m/km, a relative relief of (0.8) m/km, a ruggedness number of (277), and an average slope of (2.8) degrees. The research emphasizes the importance of addressing environmental risks in the region, such as floods and erosion, and recommends establishing water harvesting projects through dams and implementing soil conservation initiatives to protect vegetation and soil.
Keywords: Morphometric analysis; Geomorphological analysis; Abo-Habl Basin; hydrological parameters